2023
DOI: 10.1111/jnc.15980
|View full text |Cite
|
Sign up to set email alerts
|

Leptin prevents aberrant targeting of tau to hippocampal synapses via PI 3 kinase driven inhibition of GSK3β

Kirsty Hamilton,
Kate Morrow,
Ermione Markantoni
et al.

Abstract: Amyloid‐β (Aβ) and hyper‐phosphorylated tau are key hallmarks of Alzheimer's disease (AD), with an accumulation of both proteins linked to hippocampal synaptic dysfunction. Recent evidence indicates that Aβ drives mis‐localisation of tau from axons to synapses, resulting in AMPA receptor (AMPAR) internalisation and impaired excitatory synaptic function. These tau‐driven synaptic impairments are thought to underlie the cognitive deficits in AD. Consequently, limiting the synapto‐toxic effects of tau may prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Some obesity‐related brain changes may be caused by dysregulation of adipokines such as leptin, which are secreted by adipose tissue and can influence plasticity, neurogenesis and inflammatory cytokine production in dementia‐relevant brain regions such as the hippocampus 205 . Studies in AD models have suggested that leptin may have a therapeutic role in reducing Aβ and intracellular tau phosphorylation, thereby preventing synaptic dysfunction 190,191,206–208 . Work in wild‐type animals suggests that the developmental timing of obesity may be important, since poor diet (high‐fat or high sugar) in adolescence, more than in adulthood, causes cognitive defects 209 .…”
Section: Cardiometabolic Modifiable Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some obesity‐related brain changes may be caused by dysregulation of adipokines such as leptin, which are secreted by adipose tissue and can influence plasticity, neurogenesis and inflammatory cytokine production in dementia‐relevant brain regions such as the hippocampus 205 . Studies in AD models have suggested that leptin may have a therapeutic role in reducing Aβ and intracellular tau phosphorylation, thereby preventing synaptic dysfunction 190,191,206–208 . Work in wild‐type animals suggests that the developmental timing of obesity may be important, since poor diet (high‐fat or high sugar) in adolescence, more than in adulthood, causes cognitive defects 209 .…”
Section: Cardiometabolic Modifiable Risk Factorsmentioning
confidence: 99%
“… 205 Studies in AD models have suggested that leptin may have a therapeutic role in reducing Aβ and intracellular tau phosphorylation, thereby preventing synaptic dysfunction. 190 , 191 , 206 , 207 , 208 Work in wild‐type animals suggests that the developmental timing of obesity may be important, since poor diet (high‐fat or high sugar) in adolescence, more than in adulthood, causes cognitive defects. 209 With a short 21‐day lifespan and high amenity to genetic manipulation, C. elegans models of aging and human Aβ overexpression hold future promise for investigating food intake and fat accumulation relevant to obesity (reviewed in Ref.…”
Section: Cardiometabolic Modifiable Risk Factorsmentioning
confidence: 99%